Managerial Ability and Investment Efficiency among Firms Listed at the Nairobi Securities Exchange - Ongoro, Morgan; Aduda, Josiah; Wanjare, Joshua; Irungu, Morris (Journal of Finance and Accounting, 2023)
The level of managerial ability that a firm possesses may to a large extend influence its investment efficiency. The purpose of this article is to argue that managerial ability has a significant relationship with the level of firm investment efficiency. Based on a data set of 702 firm year observations for the financial period 2008- 2020, the researchers investigated whether managerial ability (MA) is associated with investment efficiency (IE). The relationship between the independent and dependent variables was tested using multivariate fixed effect panel data regression models. In addition, the researchers included firm level characteristics as its control variables given that they are known to have an association with Investment efficiency in the regression models. The findings reveal that managerial ability had a significant negative relationship with investment efficiency and that higher managerial ability was associated with lower investment efficiency. It was established that firms with higher managerial ability were more likely to overinvest compared to those with lower managerial ability. The findings also revealed that majority of listed firms in Kenya were managed by skilled managers with ability (56%) whereas the remaining 44% were found to be managed by managers with low skills and ability. The scope of the study was on one developing country. There is need for additional studies that will focus on other jurisdictions. The study recommends targeted continuous learning especially on investment efficiency. The study recommends managers to set precise investment goals and implement a comprehensive strategic plan on how to efficiently allocate and prioritize resources. The findings further reiterate the need for firms to not only hire skilled professionals but to also encourage them to set up investment teams within their various business units. The role of these teams should include; continuous evaluation of project risk and return, utilization of technological innovations to improve operational efficiency and adoption of data driven decision making policies. The study emphasizes the importance of isolating individual managerial ability from the general firm efficiency level and the contribution of these specific managerial ability on the quality of firm investment efficiency. Keywords: Investment Efficiency, Disclosure Quality, Listed Firms in Kenya